Construction of even-dimensional lattices of full diversity - Andrade, Antonio A. [UNESP]; Interlando, J. Carmelo (Academic Publications, 2019)
In this work even-dimensional ideal lattices of full diversity are obtained via the twisted homomorphism of the ring of integers of a totally real subfield of (ζp), where p is an odd prime.
Keywords: Cyclotomic fields; Lattices; Modulation schemes